2017
DOI: 10.3390/rs9121285
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and Reducing the DOA Estimation Error Resulting from Antenna Pattern Deviation for Direction-Finding HF Radar

Abstract: High-frequency (HF) radars are routinely used for remotely sensing ocean surface currents. However, the performance of the most widely used direction-finding HF radar is degraded due to the effect of the inevitable deviations of actual antenna pattern on the direction of arrival (DOA) estimation. In this paper, we quantify the DOA estimation error resulting from the deviation of the actual antenna pattern from the ideal one. Theoretical analysis and field experiment results suggest that the ratio of the deviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…There are two commonly used types of HFR observation systems: Beam-forming (e.g., CODAR and ocean state measuring and analyzing radar (OSMAR) system) and direction-finding (e.g., WERA HFR system) [26][27][28]. The former HFR system uses a distributed array of elements to electronically scan ocean surface with a relatively narrow beam; while the latter HFR system uses a small-aperture antenna to from a quite broad beam for obtaining sea echoes [29]. A land-based CODAR HFR observation system consisting of two radars has been deployed in the Galway Bay area since 2011, as shown in Figure 1.…”
Section: Radar Datamentioning
confidence: 99%
“…There are two commonly used types of HFR observation systems: Beam-forming (e.g., CODAR and ocean state measuring and analyzing radar (OSMAR) system) and direction-finding (e.g., WERA HFR system) [26][27][28]. The former HFR system uses a distributed array of elements to electronically scan ocean surface with a relatively narrow beam; while the latter HFR system uses a small-aperture antenna to from a quite broad beam for obtaining sea echoes [29]. A land-based CODAR HFR observation system consisting of two radars has been deployed in the Galway Bay area since 2011, as shown in Figure 1.…”
Section: Radar Datamentioning
confidence: 99%
“…The derivation above assumes that the complex scaling γne,i is fixed for each element ne. However, it has been noted in the literature that array element pattern changes due to mutual coupling are dependent on the bearing of the impinging signal [32, 33]. Therefore, it is likely that the complex scaling and the calculated correction factors have a bearing‐dependence as well.…”
Section: In‐field Calibration Of Passive Radar Arraymentioning
confidence: 99%
“…The direction of arrival (DOA) estimation is a key measure of HF radar performance. Through both theoretical and experimental analysis, Lai et al [6] found that the DOA error significantly depends on the ratio of the antenna pattern deviations of two loops for a cross-loop system. Based on this finding, the authors proposed a new method which takes advantage of time-averaged local spatial coverage rate (TLSCR) for mitigating the DOA estimation error.…”
Section: Overview Of Contributionsmentioning
confidence: 99%